Menilik Jejak Dinasty Abbsiyyah dalam perspektif Sejarah, Priodisasi, dan Sisitem Pemerintahan yang mewarnai Peradapan Islam - Fajriyanur, Ivan; Alawilhuda, Muhammad (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2025)
Analyzing the history, evolution and political structure of the Abbasid Dynasty is the aim of this research. From 132 AH (750 AD) to 656 AH (1258 AD), the Abbasid dynasty ruled for five centuries, which is a long time. The Abbasid dynasty was divided into five phases throughout its history, and each of these periods had a different government structure due to changing political, social, and cultural conditions. Under the leadership of Harun al-Rasyid, Muslims were successful and triumphant throughout the period of the Abbasid Caliphate in the fields of science and culture, economy, power and civilization. However, in the fifth phase, which lasted from around 1199 to 1258 AD, political conflict caused the economic decline of the Abbasid dynasty, the emergence of small dynasties, conflict, and the continuation of protracted crusades. Additionally, Mongol and Tartar troops looted every center of knowledge and power, resulting in the gradual fall of the Abbasid dynasty.